From LD to Degree: Effective techniques for the Student with a Learning Disability - Del Viscovo, Joshua A. (Journal of the American Academy of Special Education Professionals, 2009)
The purpose of this article is to espouse and highlight some essential ingredients for a student with learning disabilities and differences to survive outside of the K-12 setting. Many students with LD move to colleges and universities throughout the United States, and perhaps even the world. As they earn undergraduate and even graduate degrees, they are clearly using many techniques of self-support to complement their areas of need. This article will focus on the key skills that an LD students needs to thrive and be successful to go on to earn advanced degrees and certifications in very challenging fields. The perspective put forth in this article is one of a firsthand encounter. I, (Josh) the author of this piece can attest first hand to the challenges of going on to college, graduate school then enrolling in a Doctorate program. It is the goal to provide students and teachers alike with a general sketch of how to prepare students for college.